Comparison of Success Levels of Jump Float Service and Jump Topspin Serve in Junior Volleyball Games - Benijar Pahrul Huda; Anggi Setia Lengkana; Entan Saptani (Tadulako Journal Sport Sciences And Physical Education, 2026)
This study aimed to compare the success rates of the jump float serve and jump topspin serve among early adolescent volleyball athletes aged 11–15 years. A quantitative approach with a descriptive comparative design was employed. The population consisted of 96 athletes from the Tanjungsari Volleyball Club, with a sample of 20 male athletes selected through purposive sampling. Data were collected using the AAHPER Volleyball Serving Accuracy Test and analyzed through descriptive statistics, the Shapiro–Wilk normality test, and the Paired Sample t-Test. The results showed that the jump float serve produced a higher mean score (M = 19,30, SD = 3,74) than the jump topspin serve (M = 15,15, SD = 5,59). The normality test confirmed that the data met the assumption of normality (p > 0.05). Furthermore, the Paired Sample t-Test revealed a statistically significant difference between the two serving techniques, t (19) = 4,518, p < 0,001, with a large effect size (Cohen’s d = 1,01). These findings indicate that the jump float serve provides greater serving accuracy and consistency than the jump topspin serve in early adolescent athletes. The superiority of the jump float serve is likely related to the developmental characteristics of young athletes, whose motor control and coordination generally mature earlier than the physical and technical capacities required for more complex power-based serving techniques. Therefore, coaches are encouraged to prioritize jump float serve mastery as a foundation for technical development before gradually introducing jump topspin serve according to athletes’ biological and neuromuscular readiness.